Experimental investigation of heterogeneous hydrolysis with Zn vapor under a temperature gradient. (23rd March 2017) - Lindemer, Matthew D.; Advani, Suresh G.; Prasad, Ajay K.
Abstract: The hydrolysis step of the Zn/ZnO thermochemical cycle for hydrogen production is experimentally investigated in a laboratory-scale tube-reactor. The current work uses a new approach in which the heterogeneous oxidation of gaseous Zn with steam is carried out under a negative axial temperature gradient in order to improve cycle efficiency by reducing the proportion of steam and inert carrier gas used. It is shown that complete conversion of Zn to ZnO is possible at steam-to-Zn stoichiometries greater than 5.0. As the steam-to-Zn stoichiometry approaches unity at reduced inert gas fractions, condensation of Zn on the reactor walls becomes more likely. In addition, the observed gas-phase equilibrium shift toward increased production of ZnO at temperatures under 800 K is consistent with earlier theoretical predictions. While complete conversion with low inert gas and steam usage was not achieved, our approach shows great improvement over previous aerosol-based approaches when considering the total amounts of steam and inert gas used per unit of hydrogen produced. Therefore, the current temperature gradient approach is promising for the design of an efficient reactor for water splitting via Zn vapor. Highlights: Heterogeneous hydrolysis with Zn vapor studied under negative temperature gradient. High degree of Zn to ZnO conversion observed at high H2 O to Zn ratios. Equilibrium shift toward formation of ZnO observed at lower temperatures. Significant Zn condensation observed with lower amounts of steam and inert gas. H2 produced per unit of steam and inert gas used is higher than in prior work.